Influence of Attachment Styles on Academic Performance of Adolescents in High Cost Private Secondary Schools in Nairobi County, Kenya - Majimbo, Evelyn (European Scientific Journal, ESJ, 2017)
The purpose of the study was to determine the effect of adolescent attachment styles on academic performance in high-cost private secondary schools. The specific objectives were: to establish the attachment styles exhibited by the adolescents, to determine the relationship between attachment styles and academic performance of students in selected high cost secondary schools in Nairobi and to assess the role of parental bonding on adolescent attachment. Descriptive research design was used. The target population was students drawn from high cost private secondary schools in Dagoreti, Langata and Westlands constituencies in Nairobi County, Kenya. Data was collected by aid of a structured questionnaire with closed and openended questions. Data was analyzed using correlation technique and Mann- Whitney U test. The results showed that there was a weak positive correlation between academic performance and secure attachment style and a negative correlation between academic performance and insecure attachment style. In overall, securely attached adolescents performed better than their insecure attached counterparts. Parents placed too much expectation on their adolescents which increased their anxiety and stress during exams. The implication of this is that parents unknowingly cause psychological harm by pushing their adolescents too much to excel in their education. Counseling practitioners attached to high cost private secondary schools should adopt a tripartite framework of guidance and counseling that involves the participation of parents through mutual understanding and child-centered engagement. Parents of these children should also be realistic even when they set their well-intended bar high for their adolescent children.